Soymilk plain beverages: correlation between acceptability and physical and chemical characteristics - Marcela Moreira TERHAAG (Ciência e Tecnologia de Alimentos, 2013)
The objective of the research was to relate the physical and chemical characteristics of soymilk plain beverages to its sensoryacceptance. Five commercial products and a new product formulated based on the less accepted sample were used. The overallacceptance was evaluated by 102 assessors using a 10-point hybrid hedonic scale. The hedonic scores ranged from 3.8 (sample E)to 7.0 (A). Most assessors (55%) preferred sample A, which was viscous (26.6 cp), dark (L* = 77.7), and slightly acidic (pH = 6.6).Sample C, which had lower solid content and higher acidity, was preferred by 29% of the assessors. These two beverages showedthe greatest commercial potential of the products analyzed. The least-accepted sample (E), preferred by 8% of the assessors,had a lighter color (L* = 96.8), lower viscosity (13.5 cp), higher lipid content (2.2 g/100 g), and less protein (1.68 g/100 g) thanthe other products evaluated. A reformulation of the least preferred product (E) with the addition of maltodextrin and alsovanilla and milk flavors increased its acceptance, yielding an average score of 7.2. Overall, it was observed that a soymilk plainbeverage with higher viscosity, darker color, and higher protein content best meets consumer expectations.